PerC Manipulates Metabolism and Surface Antigens in Enteropathogenic Escherichia coli - Mellies, Jay L.; Platenkamp, Amy; Osborn, Jossef; Ben-Avi, Lily (Frontiers in Cellular and Infection Microbiology, 2017)
Enteropathogenic Escherichia coli is an important cause of profuse, watery diarrhea in infants living in developing regions of the world. Typical strains of EPEC (tEPEC) possess a virulence plasmid, while related clinical isolates that lack the pEAF plasmid are termed atypical EPEC (aEPEC). tEPEC and aEPEC tend to cause acute vs. more chronic type infections, respectively. The pEAF plasmid encodes an attachment factor as well as a regulatory operon, perABC. PerC, a poorly understood regulator, was previously shown to regulate expression of the type III secretion system through Ler. Here we elucidate the regulon of PerC using RNA sequencing analysis to better our understanding of the role of the pEAF in tEPEC infection. We demonstrate that PerC controls anaerobic metabolism by increasing expression of genes necessary for nitrate reduction. A tEPEC strain overexpressing PerC exhibited a growth advantage compared to a strain lacking this regulator, when grown anaerobically in the presence of nitrate, conditions mimicking the human intestine. We show that PerC strongly down-regulates type I fimbriae expression by manipulating fim phase variation. The quantities of a number of non-coding RNA molecules were altered by PerC. In sum, this protein controls niche adaptation, and could help to explain the function of the PerC homologs (Pch), many of which are encoded within prophages in related, Gram-negative pathogens.